Equity in access to exercise tolerance testing, coronary angiography, and coronary artery bypass grafting by age, sex and clinical indications. Issue 6 (1st June 2001) - Bowling, A; Bond, M; McKee, D; McClay, M; Banning, A P; Dudley, N; Elder, A; Martin, A; Blackman, I
Abstract : OBJECTIVES: To assess whether patients with heart disease in a single UK hospital have equitable access to exercise testing, coronary angiography, and coronary artery bypass graft surgery (CABG). METHOD: Retrospective analysis of patients' medical case notes (n = 1790), tracking each case back 12 months and forward 12 months from the patient's date of entry to the study. SETTING: Single UK district hospital in the Thames Region. PATIENTS: Patients (elective and emergency) with a cardiac ICD inpatient code at discharge or death, or who were referred to cardiology or care of the elderly unit over a 12 month period in 1996–7 (new episodes) were included. RESULTS: Analysis of 1790 hospital case notes revealed that, despite having indications for intervention identical to those of younger patients, older patients (that is, those aged > 75 years) and women, independently, were significantly less likely to undergo exercise tolerance testing (exercise ECG) and cardiac catheterisation. The similar trends for age and access to CABG did not achieve significance. While clinical priority scores also independently predicted access to cardiac catheterisation and CABG, considerable numbers of patients in high clinical priority groups were not referred for either procedure. CONCLUSIONS: The management and treatment of older patients and women with cardiac disease may be different from that of younger patients and men. Given the similarity of the indications for treatment and the lack of significant contraindications or comorbidities as a cause for these differences, one possible explanation is that these patients are being discriminated against principally because of their age and sex. Although clinical priority scores independently predicted access to catheterisation and CABG, large proportions of patients in high priority groups were not referred. This implies that the New Zealand priority scoring system may be more equitable than UK practice. The cost implications of redressing these inequities in service provision would be considerable.